Competitive universities need to internationalize learning: Perspectives from three European universities - Ana Maria Lara; Keith Stuart; Jan Karpe; Heide Faeskorn-Woyke; Raúl Poler; Rafael Brotons (Journal of Industrial Engineering and Management (JIEM), 2009)
The process of restructuring European universities in order to harmonize their educational systems is rapidly approaching a key milestone as 2010 looms large on the horizon. This paper describes an approach to the European Higher Education Area (EHEA) based on a real case study of students that belong to five European Universities (University of Burgos, Technical University of Valencia, University of Valladolid, University of Basque Country and University of Applied Sciences Cologne). The objective of this paper is two-fold: on the one hand, to analyze from the student's point of view how they value the restructuring of teaching as a result of the Bologna process and what are the implications for students with regards to both their academic qualifications and their future incorporation into the labour market; and, on the other hand, to deduce from the results obtained recommendations which may help to guide teachers towards successful internationalization and collaboration between interuniversity networks, as well as achieving greater standards of quality within university teaching. Only this would permit an environment in which students are capable of developing the necessary competences, and put into practice learning outcomes. The results show that students value communication, innovative proposals and cooperation between universities; the internationalization of knowledge between universities has been positively accepted and this has motivated research to place a stronger focus on this aspect; it impacts strongly on scientific productivity, improves the quality of education offered by the teaching staff, and leads to greater student mobility. This strategy is intrinsically linked to learning from local experiences shared by members of the same university as well as from more global experiences made available through inter-university networks. It implies being willing to listen, to communicate, to engage in dialogue and means that we must seek to understand the potential contributions from teachers, staff and students that make up each university.
Keywords: 650; bologna process; european higher education; competitive universities; internationalisation